Tracing Language in Traditional Fisheries: Identity, Functions, and Oral Heritage of Maluku Fishermen - Hiariej, Chrissanty; Hehanussa, Kedswin G. (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
Language that develops within coastal communities is the result of long-term interaction between humans and the marine environment. In fishermen’s lives, language functions not only as a means of communication, but also as a medium for storing ecological knowledge, shaping cultural identity, and transmitting social values. This study aims to analyze the role of language in the lives of Maluku fishermen, particularly in relation to the formation of coastal community identity, the function of language in fishing activities, and the existence of oral traditions as part of maritime cultural heritage. This study employs a descriptive qualitative approach using literature review and conceptual analysis of various forms of language use in traditional fisheries. The data consist of fishermen’s vocabulary, terms for naming marine spaces, and forms of oral traditions such as folklore, mantras, pantun, and maritime proverbs found in coastal communities. The results show that the language of Maluku fishermen has broad functions in coastal community life. It serves not only as a technical communication tool in fishing activities, but also as a marker of community identity and a medium for storing ecological knowledge related to marine conditions, fishing seasons, and traditional fishing strategies. In addition, language functions as a medium of cultural expression reflected in various forms of oral traditions passed down through generations. From an ecolinguistic perspective, the marine lexicon used by fishermen represents the reciprocal relationship between humans and the maritime environment. Therefore, documenting and preserving fishermen’s language is an important step in maintaining maritime cultural identity while sustaining local ecological knowledge that supports sustainable marine resource management.